Pengembangan Flipbook Berbasis Problem Based Learning Terintegrasi Augmented Reality pada Materi Virus Kelas X di SMA - Putu Meli Lestari Anggreni; I Made Sutajaya; I Wayan Sukra Warpala (Syntax Idea, 2026)
This study aims to develop a flipbook learning media based on Problem Based Learning (PBL) integrated with Augmented Reality (AR) technology on the topic of viral material in class X of high school, and measure the level of validity and practicality of the product produced. This research was carried out using the Research and Development (R&D) method and ADDIE development model which consisted of: analyze, design, development, implementation, and evaluation stages. The research subjects consisted of: 2 material experts, 2 media experts, 3 biology teachers, and 30 students of class X of SMA Negeri 1 Kubutambahan. The instruments used were in the form of validity test questionnaires and practicality test questionnaires. Data were analyzed using quantitative descriptive techniques using the calculation of the Gregory validity coefficient and the percentage of practicality. The results of the study showed that the flipbook media developed was in the category of very valid with a Gregory Validity Coefficient (KVG) value of 1.00 based on the material and media aspects. In addition, the results of the practicality test also showed a very practical category with an average percentage of 91.2% based on the results of teacher assessments and 86.9% based on student assessments. This flipbook media has the advantages of attractive visual display, easy-to-use navigation, and the integration of interactive features such as videos, quizzes, and augmented reality can illustrate abstract material concepts into more concrete. Thus, the flipbook learning media based on Problem Based Learning (PBL) that is integrated with Augmented Reality (AR) for the virus material developed is declared valid and practically applied as a biology learning medium, has the potential to improve understanding of material concepts, and motivate students to be actively involved in the learning process